2011
DOI: 10.1161/circresaha.111.244046
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase-Resistant Gap Junctions Inhibit Pathological Remodeling and Prevent Arrhythmias

Abstract: Rationale Post-translational phosphorylation of connexin43 (Cx43) has been proposed as a key regulatory event in normal cardiac gap junction expression and pathologic gap junction remodeling. Nonetheless, the role of Cx43 phosphorylation in the context of the intact organism is poorly understood. Objective To establish whether specific connexin43 phosphorylation events influence gap junction expression and pathologic remodeling. Methods and Results We generated Cx43 germline knock-in mice in which serines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 53 publications
9
133
1
Order By: Relevance
“…As shown in Figure 1 Experimental Protocol With Trabeculae Non-uniform muscle contraction was produced with a 2,3-butanedione monoxime (BDM) jet as previously reported. 3, 28 The equivalent diffusion coefficient for fura-2 was first calculated without electrical stimulation before, just after, and 1 h after superfusion with 5 …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1 Experimental Protocol With Trabeculae Non-uniform muscle contraction was produced with a 2,3-butanedione monoxime (BDM) jet as previously reported. 3, 28 The equivalent diffusion coefficient for fura-2 was first calculated without electrical stimulation before, just after, and 1 h after superfusion with 5 …”
Section: Resultsmentioning
confidence: 99%
“…The only available report to date using this approach showed that mice in which Cx43 was replaced by a Cx43 mutant at the CK1 sites in which serines 325/328/330 were replaced with phosphomimetic glutamic acids (S3E) were resistant to gap junction remodeling and less susceptible to the induction of arrhythmias. In contrast, mice in which a Cx43 mutant with serines 325/328/330 mutated to non-phosphorylatable alanines (S3A) was knocked-in in place of Cx43 had severe alterations in gap junction formation and function, and had a proarrhythmic phenotype (Remo et al, 2011). This report shows a mechanistic link between the phosphorylation state of Cx43 and arrhythmic susceptibility (Remo et al, 2011).…”
Section: Genetic Modification Of a Phosphosite-specific Mutant Connexinmentioning
confidence: 80%
“…In contrast, mice in which a Cx43 mutant with serines 325/328/330 mutated to non-phosphorylatable alanines (S3A) was knocked-in in place of Cx43 had severe alterations in gap junction formation and function, and had a proarrhythmic phenotype (Remo et al, 2011). This report shows a mechanistic link between the phosphorylation state of Cx43 and arrhythmic susceptibility (Remo et al, 2011).…”
Section: Genetic Modification Of a Phosphosite-specific Mutant Connexinmentioning
confidence: 80%
See 1 more Smart Citation
“…In recent years the role of miRNAs in cancer has been demonstrated in many types of tumors including glioblastomas where they can control processes such as proliferation, invasion, angiogenesis and apoptosis [12] . Interestingly, some miRNAs involved in gliomagenesis downregulate Cx43 expression.…”
Section: "Micrornasmentioning
confidence: 99%